2004
DOI: 10.1096/fj.03-0319fje
|View full text |Cite
|
Sign up to set email alerts
|

Gating of the polycystin ion channel signaling complex in neurons and kidney cells

Abstract: Mutations in either polycystin-2 (PC2) or polycystin-1 (PC1) proteins cause severe, potentially lethal, kidney disorders and multiple extrarenal (including brain) disease phenotypes. PC2, a member of the transient receptor potential channel superfamily, and PC1, an orphan membrane receptor of largely unknown function, are thought to be part of a common signaling pathway. Here, we show that in rat sympathetic neurons and kidney cells, coassembly of full-length PC1 with PC2 forms a plasmalemmal ion channel signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
183
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 165 publications
(185 citation statements)
references
References 38 publications
2
183
0
Order By: Relevance
“…Activation through PKD1-Following up on the work of Hanaoka et al [29], Delmas et al [35] confirmed that PKD1 promoted the targeting of PKD2 to the plasma membrane. Moreover, they showed that addition of a monoclonal antibody (MR3) against a portion of the extracellular domain of PKD1 (amino acid residues 2938 -2956), which is in close proximity to a domain homologous to the receptor for egg jelly (REJ) further augmented the activity of the PKD1/ PKD2 complex.…”
Section: Modes Of Pkd2 Activationmentioning
confidence: 95%
See 4 more Smart Citations
“…Activation through PKD1-Following up on the work of Hanaoka et al [29], Delmas et al [35] confirmed that PKD1 promoted the targeting of PKD2 to the plasma membrane. Moreover, they showed that addition of a monoclonal antibody (MR3) against a portion of the extracellular domain of PKD1 (amino acid residues 2938 -2956), which is in close proximity to a domain homologous to the receptor for egg jelly (REJ) further augmented the activity of the PKD1/ PKD2 complex.…”
Section: Modes Of Pkd2 Activationmentioning
confidence: 95%
“…It allowed non-selective passing of cations, with slightly higher selectivity for Ca 2+ over Na + and K + , but higher conductance in K + [34]. However, the high single channel conductance (100-200 pS) [24,31,35] in combination with the relatively high open probability (~20-40%) [24,31,35] did not correlate well with the moderate amplitude of whole cell currents (several hundreds pA at -100 mV) in cells overexpressing PKD2 [35,36]. This, along with the observation that the vast amount of PKD2 was in the ER [25] raised the question of whether PKD2 alone or even in combination with PKD1 could actually form a functional channel in the plasma membrane.…”
Section: Functional Compartmentalization Of Pkd2mentioning
confidence: 99%
See 3 more Smart Citations